Surgical Treatment Compared to Conservative Treatment in Remission of Pain and Hyposthesia in Tarsal Tunnel Syndrome – Systematic Review - Marcelo José da Silva de Magalhães; Iara Cristina Vieira Ribeiro; Márcio de Mendonça Cardoso; Ricardo de Amoreira Gepp (Brazilian Neurosurgery, 2022)
Introduction Tarsal tunnel syndrome (TTS) is caused by compression of the posterior tibial nerve. Objective To evaluate the effectiveness of surgical treatments compared to conservative treatments in reducing the symptoms of the syndrome. Methods The PubMed, Lilacs, Cochrane Library, and PEDro databases were used for this review. Results Only 11 articles were selected. Conclusion The most common causes of TTS identified were presence of ganglia, bone prominence causing a talocalcaneal collision, trauma, varicose and idiopathic veins. The main symptom was pain in the medial plantar region and paresthesia that can radiate to the fingers or to the calf. Most patients have a positive Tinel sign upon physical examination. Electrodiagnostic test usually shows the presence of latency in sensory nerve conduction. There is no consensus suggesting that a longer time between diagnosis and surgical treatment leads to worse prognosis. In the group of operated patients, the ones who benefited most from the procedure were those who had a structure such as ganglion, cysts, or varicosities causing compression. The most cited surgical complications were postsurgical wound infection, wound dehiscence, and calcaneus hypoesthesia. Regarding surgical techniques, the release of the posterior tibial nerve via endoscopy had a favorable outcome in relation to the symptoms of pain and hypoesthesia, with no reports of infection of the operative site in the articles identified in this review. We observed a rate of good or excellent pain control of 68% (n = 204) for open surgery (n = 299), 100% (n = 8) for endoscopic surgery (n = 8), and 7% (n = 2) for conservative treatment (n = 28).